Aplikasi Decision Support System (DSS) dengan Metode Fuzzy Multiple Attribute Decission Making (FMADM) Studi Kasus : AMIK Indonesia Dan STMIK Indonesia - Mukhtar Mukhtar; Munawir Munawir (KITA Institute, 2018)
Educational institutions such as AMIK Indonesia and STMIK Indonesia often require a form of the decision in determining academic judgment on the elements of tri dharma; teaching, research, community service and supporting elements that are appropriate for academics so that good quality education is achieved in accordance with the assessment. A decision is a matter that is very influential in the process of facing the chosen alternative, so also choosing the academic quality that has an impact on the focus of accreditation of higher education institutions. The model used in this decision support system is Fuzzy Mutual Attribute Decision Making (FMADM) and the method used is Simple Additive Weighting (SAW), which is looking for weighted sums of performance ratings on each alternative on all attributes. The purpose of this study is to design a system of academic judgment decision support with Fuzzy Mutual Attribute Decision Making (FMADM) systems with Simple Additive Weighting (SAW) Method, to obtain more accurate results in an academic assessment of AMIK Indonesia and STMIK Indonesian tri dharma elements so that they can improve the quality of universities. Broadly speaking, this study uses data collection methods through literature studies, interviews and direct observation to AMIK Indonesia and STMIK Indonesia Banda Aceh. While the research design uses experimental because it produces a product that is a decision support system. The method used to support this research is the FMADM method using the SAW method calculation. Supporting applications that will be created with the author using web-based programming languages such as; HTML, CSS, Jquery, JSON and MySQL databases with Windows operating systems. On running analysis and system design that will be created the author is described by Microsoft Visio 2016. The method used to evaluate the system is the black box method where the black box testing focuses on system functions.